Effect of light illumination on antiferromagnet-metamagnet phase transitions in the garnet Ca3Mn2Ge3O12 - Bedarev, V. A.; Gapon, V. I.; Gnatchenko, S. L.; Baran, M.; Szymczak, R.; Desvignes, J. M.; Gall, H. Le (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The effect of linearly polarized light illumination on the metamagnetic phase transition in the antiferromagnetic garnet Ca3Mn2Ge3O12 is studied. The crystal is exposed to light propagating both along the tetragonal axis [001] and along the [100] direction. In both cases, a change of the field Ht of the metamagnetic phase transition is observed under illumination, and this change depends on the orientation of plane of polarization of the light with respect to the crystal axes. In the first case, k||H||[001], the value of Ht decreases on exposure to light with the polarization E||[110] and increases on exposure to light with the polarization E||[11̅0]. In the second case, k||H||[100], the value of Ht decreases irrespective of the orientation of the plane of polarization of the light with respect to the crystal axes. However, the magnitudes of the change of Ht are different for light with the polarization E|| [011] and with the polarization E||[01̅1]. The change of the field of the metamagnetic phase transition in the second case was much larger than in the first case. A phenomenological theory of the photomagnetic effects observed in the antiferromagnetic garnet Ca3 Mn2Ge3O12 is developed. It is shown that the effect of light illumination on the metamagnetic phase transition is related to the photoinduced magnetic moment in this antiferromagnet. The magnetic moment induced by linearly polarized light in the garnet Ca3Mn2Ge3O12 is detected experimentally by means of a SQUID magnetometer.